Microvascular Thrombosis and Ischaemic Limb Losses in Critically Ill Patients - Warkentin, Theodore E. (Hämostaseologie, 2019)
Relatively little scientific attention has been given to the small subset of critically ill patients with circulatory shock who develop ischaemic limb losses (symmetrical peripheral gangrene [SPG]). The clinical picture consists of acral (distal extremity) tissue necrosis involving lower limbs in a largely symmetrical fashion and with detectable arterial pulses; in one-third of patients the upper extremities are also affected (potential for four-limb amputations). The laboratory picture includes thrombocytopenia, coagulopathy, and normoblastemia (circulating nucleated red blood cells). The explanation for limb losses is microvascular thrombosis caused by disseminated intravascular coagulation usually secondary to cardiogenic or septic shock. A common myth is that vasopressors cause the ischaemic limb injury. However, the more likely explanation is failure of the natural anticoagulant systems (protein C and antithrombin) to downregulate thrombin generation in the microvasculature. This is because more than 90% of patients with SPG have preceding ‘shock liver’, which occurs 2 to 5 days (median, 3 days) prior to ischaemic limb injury, with impaired hepatic production of protein C and antithrombin.
Keywords: acute ischaemic hepatitis (‘shock liver’); antithrombin; disseminated intravascular coagulation; protein C; symmetrical peripheral gangrene; vasopressors